Penguatan Nilai Integritas melalui Penyuluhan Pendidikan Karakter dan Antikorupsi di Sekolah Dasar dan Menengah - Suhria Suhria; Meli Meli; Erni Nurdin (Journal of Social Responsibility Projects by Higher Education Forum, 2025)
−This Community Service Program aims to increase awareness of the value of integrity and prevent corrupt behavior from an early age in elementary and secondary school students. Located in Tolitoli Regency, Central Sulawesi, the counseling was carried out by the author and in collaboration with STKIP lecturer and student Abdul Mujib Laewang with three partner schools. The method used is counseling to partner schools, carried out collaboratively between writers, lecturers and students of Semester III of STKIP Abdul Mujib Laewang Dampal Selatan. The counseling activities were carried out for three days, on January 4-6, 2025, at three school locations, namely MI Nurul Ilmi Hidayatullah, SDN 2 Tampiala, and SMPN 1 Dampal Selatan. The material presented includes character values, integrity/anti-corruption values, as well as factors, impacts, and prevention of corrupt behavior in schools. The results of the activity showed a significant increase in understanding in 118 student participants related to the values of integrity and identification of corrupt behavior in the school environment, as well as active participation in discussions